OBJECT-ORIENTED PROGRAMMING IN C++ - Tetyana, Sopronyuk (CreateSpace, 2014)
The textbook is intended to be used in the computer science course of “Object-oriented programming in C++”. It contains all the information needed for completing assignments and labs. This textbook covers fundamental concepts in object-oriented programming: objects, classes, and inheritance. This book shows how objects are instantiated from a class, and how new classes are inherited. It introduces constructors, public and private methods, abstract, base and inherited classes, hierarchy of classes, method overloading. Detailed examples with comments are provided. This textbook is intended for educational purposes.
Keywords: class, object, encapsulation, polymorphism, inheritance